The properties director's toolkit creativity, collaboration and communication for prop shop management in the theatre and performing arts - Strawn, Sandra J.; Schlenker, Lisa (New York Routledge, 2018)
"Regardless of your profession, whether you're a Stage Manager or Stagehand, The Focal Press Toolkit Series has you covered. With all the insider secrets, paperwork, and day-to-day details that you could ever need for your chosen profession or specialty, these books provide you with a one-stop-shop to ensure a smooth production process." -- Publisher's description
Sense and sensibility -- Job titles and duties -- Working in film -- What is a prop? -- Pre-production and planning -- Getting started -- Working in regional theatre -- Budgeting -- The build process -- Working with scenic designers -- The rehearsal and production process -- Working with stage management -- The production / tech process -- Co-productions and rentals -- Working in children's theatre -- Having a career in props -- Working as a freelance prop maker -- The prop shop
"A Focal Press book"--Cover.
Includes index.
Keywords: Stage props -- Design and construction; Theaters -- Stage-setting and scenery